Omrežje slovenske ekonomske elite - Žerdin, Ali (Družboslovne razprave, 2005)
In the article we are trying to reconstruct the network of Slovene economic elite on the election day in the year 2004. Individuals in the network are linked by interlocking directorship relations. Using social network analysis we calculated key measures of centrality. Measures detecting influence of a person reveal that most central positions are occupied by individuals who were appointed on their positions by the government. Measure detecting structural prestige reveals that most central positions are merely occupied by members of Forum 21 (co-ordinated by ex-President Kučan). Results of the analysis indicate the logic of economic elite recruitment in Slovenia has deep political roots.
Keywords: Slovenia; Slovenija; družbena diferenciacija; družbena omrežja; elita; ekonomska elita; družbena elita; poslovodni delavci